Morphological and hemodynamic patterns of carotid stenosis treated by endarterectomy with patch closure versus stenting: a duplex ultrasound study - Marcia Maria Morales; Alexandre Anacleto; Marcello Azem Buchdid; Paulo Ricardo Baggio Simeoni; Sergio Ledesma; Crescêncio Cêntola; João Carlos Anacleto; Marcela Aldrovani; Carlos Eli Piccinato (Clinics, 2010)
OBJECTIVES: A duplex ultrasound study was performed to investigate morphological and hemodynamic patterns of carotid stenoses treated by endarterectomy with patch closure versus stenting. MATERIALS AND METHOD: Twenty-nine carotid stenoses were treated with stenting and 65 with patch closure. Duplex ultrasound parameters (luminal diameter, mm; peak systolic velocity and end-diastolic velocity, cm/s) were measured 24 hours after the procedures and also at 12 months post-procedure. Residual stenoses (immediately postprocedure) and restenoses (within 12 months of procedure) were defined as narrowings of >50% on duplex ultrasound examination. RESULTS: In stented patients, the luminal diameter of the proximal internal carotid artery increased in the interval between the 24-hour and 12-month post-procedure studies, while in the patch closure patients, the diameter decreased. Carotid hemodynamics normalized immediately after both patching and stenting and remained relatively stable thereafter up to 12 months. No statistically elevated flow velocities (in the absence of residual stenosis or restenosis) were observed in the patched or stented carotid arteries. No significant differences in residual stenosis rates were observed between the stenting group (3 cases, 10.34%) and the patch closure group (1 case, 1.53%, P = 0.08). At 12 months, 2 stenting patients (6.88%) and 2 patch closure patients (3.07%) had $50% restenosis (P = 0.58). One case of late stroke due to restenosis was observed in the stenting group; the patient died 12 months postoperatively, before receiving new intervention. CONCLUSION: Measurements over time in luminal diameter signalized differences in arterial remodeling mechanisms between patched and stented carotids. Both stenting and patch closure were associated with carotid patency and flow restoration. This study does not support a general approach to new velocity criteria indiscriminately applied to stented or patched carotids.